Pemanfaatan Umbi Talas Sebagai Media Pertumbuhan Bibit F0 Jamur Tiram dan Jamur Merang - Karimawati, Nurul, Suparti, M.Si (2016)
Taro tubers is one tuber that contains 23.7% carbohydrate, 1.5% fiber, 0.05% vitamin B1, 2% vitamin C, and 1.5% protein, so as to meet the nutritional needs for growth of fungal mycelium. This study aims to determine the mycelium growth oyster mushrooms and straw mushrooms seed (F0). The method of the research is kuantitative description with experimental research design. The method used was experimental research methods. The study design used CRD with factorial design consisting of two factors: F1= media concentration of 80%, 90% and 100%, and F2 = oyster mushrooms and straw mushrooms with 3 repetitions. Technique analysis data used the One Way ANOVA. Based on the results of the study, the average diameter of oyster mushrooms mycelium growth and straw mushrooms on M1J1 treatment that is 5.9 cm, M2J1 of 6.9 cm, M3J1 of 6.3 cm, M1J2 of 1.5 cm, M2J2 of 2.6 cm, and the M3J2 of 2.3 cm. Based on the results of this study explained that the oyster mushrooms mycelium F0 seed and straw mushrooms can grow at 90% taro tubers media, but the media taro tubers 90% of the nicest on oyster mushrooms mycelium.